Differentiated Advertising, Heterogeneous Consumers and Suitable Design of Platform Merchant - Xuefeng Zhang; Ji Luo; Xiao Liu (Mathematics)
The limited endowment of initial traffic creates fierce competition among merchants for securing scarce resources in e-commerce platforms. Optimal pricing mechanisms are imperative to maximize transaction volumes and attract sustained traffic support from platforms. This study investigates merchant pricing mechanisms under two advertising strategies—broadband advertising and targeted advertising—by constructing differentiated pricing models that account for consumer preference heterogeneity. The findings reveal that, in most cases where merchants prioritize profit maximization, targeted advertising-driven pricing mechanisms outperform broadband advertising strategies. However, when merchants prioritize early-stage sales volume, broadband advertising proves to be more advantageous. Furthermore, the study shows that merchant pricing strategies evolve over their lifecycle, transitioning from offering lower prices to high-type consumers toward progressively higher prices, thus validating the underlying mechanism of “big data price discrimination” (the phenomenon of “killing loyal customers”). Additionally, this research emphasizes the importance of accurately understanding consumer preferences, as the sensitivity differential between price and advertising responses plays a crucial moderating role. When the sensitivity gap becomes excessively large, the price differential in differentiated pricing mechanisms should be proportionally reduced to maintain effectiveness. In conclusion, by integrating consumer utility, merchant profit, and platform incentives, pricing mechanisms based on targeted advertising exhibit superior capabilities in screening consumer information. When combined with advertising effectiveness and consumer preference heterogeneity, these mechanisms represent a relatively optimal strategy. However, this conclusion holds only when the proportion of high-type consumers in the market is moderate, not excessively low. This study contributes to the literature by providing a comprehensive framework for merchants to select appropriate pricing strategies under varying advertising environments and consumer structures.